Machiavellian Moments and the Exigencies of Leaving. Issue 2 (1st June 2021) - Ward, Stuart
Abstract: J. G. A. Pocock's magnum opus, The Machiavellian Moment, seems an unlikely contender as an intimation of Brexit. Published in 1975, his study of the revival of classical Republicanism in Renaissance Italy and the struggle to uphold a universal ideal of active citizenship could not be further removed from Britain's departure from the European Union forty-five years later. But the wider production context suggests that it might be worth probing the possible connections. This article examines Pocock's protracted reckoning with Britain's entry into the European Economic Community in the early 1970s amid the ruptures of empire's end. It seeks to tease out the existential underpinnings not only of the latter-day exigencies of leaving but also of the persistent habit of harnessing that ambition to a reimagining of Britain's global coordinates.